(untitled) (Journal of Foreign Language Studies, 2024)
This study investigated second-year English majors’ perceived benefits and challenges of note-taking when they practiced listening to English mini-lectures. Qualitative data were collected from five semi-structured interviews with English-major sophomores at a public university in Hanoi. It was found that the students were aware of the benefits of note-taking to while-and-post-listening activities and their long-term learning. The students also reported the challenges they faced while taking notes, including unfamiliar lecture topics, unfamiliar vocabulary/terminology, speaker’s accent, identifying main ideas and details, statistics, and background noise. Based on the main findings, a number of recommendations are given to assist teachers and students in enhancing their note taking skills.